2023
DOI: 10.1021/acs.jpclett.3c01321
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Goethite-Sulfide Nanowire Heterojunctions for High Current Density Water Splitting

Abstract: The preparation of efficient and stable bifunctional electrocatalysts for electrochemical overall water splitting (OWS) to scale up commercial hydrogen production remains a great challenge. Here, we synthesized heterojunction structures consisting of Co9S8/Ni3S2 nanowire arrays and amorphous goethite (FeOOH, α-phase) particles as efficient OWS catalysts using an interface engineering strategy. The interfacial charge inhomogeneity caused by the heterojunction contact leads to the generation of a built-in electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
(77 reference statements)
0
2
0
Order By: Relevance
“…The current energy demand around the globe has intensified the research for clean and renewable energy technologies that can directly abate the continuous deterioration of the environment by achieving zero CO 2 emissions. In this context, the utilization of solar energy for photocatalysis and photoelectrochemical (PEC) water splitting has attracted an extensive amount of research interest. In recent times, scientists have focused on photoactive metal oxides as emerging materials owing to their low cost, facile synthesis, and long-term stability. In the past few years, there has been an enormous amount of interest in the development of heterojunction-based composite materials, with enhanced photoactivity and redox ability. , It has been reported that the selection of materials for heterojunction formation based on their respective band edge positions is crucial to achieve favorable charge carrier dynamics. , In a typical PEC system, the hydrogen evolution reaction (HER) occurs at the photocathode [H + /H 2 at 0 V vs the reversible hydrogen electrode (RHE)], while the photoanode is responsible for the oxygen evolution reaction (OER, O 2 /H 2 O at 1.23 V vs the RHE) . Both photocatalysis and PEC water splitting involve the generation of electrons and holes under light, followed by their transport to the surface.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The current energy demand around the globe has intensified the research for clean and renewable energy technologies that can directly abate the continuous deterioration of the environment by achieving zero CO 2 emissions. In this context, the utilization of solar energy for photocatalysis and photoelectrochemical (PEC) water splitting has attracted an extensive amount of research interest. In recent times, scientists have focused on photoactive metal oxides as emerging materials owing to their low cost, facile synthesis, and long-term stability. In the past few years, there has been an enormous amount of interest in the development of heterojunction-based composite materials, with enhanced photoactivity and redox ability. , It has been reported that the selection of materials for heterojunction formation based on their respective band edge positions is crucial to achieve favorable charge carrier dynamics. , In a typical PEC system, the hydrogen evolution reaction (HER) occurs at the photocathode [H + /H 2 at 0 V vs the reversible hydrogen electrode (RHE)], while the photoanode is responsible for the oxygen evolution reaction (OER, O 2 /H 2 O at 1.23 V vs the RHE) . Both photocatalysis and PEC water splitting involve the generation of electrons and holes under light, followed by their transport to the surface.…”
mentioning
confidence: 99%
“… 10 12 In the past few years, there has been an enormous amount of interest in the development of heterojunction-based composite materials, with enhanced photoactivity and redox ability. 13 , 14 It has been reported that the selection of materials for heterojunction formation based on their respective band edge positions is crucial to achieve favorable charge carrier dynamics. 15 , 16 In a typical PEC system, the hydrogen evolution reaction (HER) occurs at the photocathode [H + /H 2 at 0 V vs the reversible hydrogen electrode (RHE)], while the photoanode is responsible for the oxygen evolution reaction (OER, O 2 /H 2 O at 1.23 V vs the RHE).…”
mentioning
confidence: 99%